Assessing aesthetic impressions with pictorial measures: A novel approach in empirical aesthetics - Ivan Z. Stojilović (i-Perception)
This study introduces pictorial technique (PT) as an innovative method in empirical aesthetics to assess aesthetic impressions of visual artworks. Forty participants, drawn from general and artistic populations, evaluated nine paintings representing abstract, traditional figural, and modern figural styles using the PT and aesthetic rating scales. The PT enabled participants to mark impactful areas within artworks, transforming subjective impressions into spatial data visualized as heatmaps. Results showed that, on average, participants marked 17% of the painting's surface, with notable stylistic differences in attention distribution. Abstract paintings exhibited dispersed attention, focusing on geometric shapes and color contrasts, while traditional figural works concentrated on narrative elements. Modern figural paintings demonstrated a hybrid pattern, emphasizing both individual details and broader compositions. The study also tested the hypothesis that dimensional characteristics of marked areas correspond to aesthetic preferences. Findings revealed that the size of marked regions modestly predicted ratings on Interestingness and Comprehensibility scales, though the explained variance was limited. The study highlights the PT's potential for visualizing aesthetic engagement and suggests its integration with physiological methods like eye-tracking to explore the interaction between spontaneous attention and reflective aesthetic judgments. These findings underscore PT's adaptability and value as a tool for investigating aesthetic experiences across diverse art forms and cultural contexts.